From family to police force: security and belonging on a South Asian border - Ibrahim, Farhana (Police/Worlds: studies in security, crime, and governance, 2021)
Policing everyday life on a border -- Militarism and everyday peace: gender, labor, and policing across "civil-military" terrains -- Policing Muslim marriage: the specter of the "Bengali" wife -- Blood and water: the "Bengali" wife and close-kin marriage among Muslims -- The work of belonging: citizenship and social capital across the Thar desert.